The Risk Assessment of Clinical Pathology Laboratory in Universitas Airlangga Hospital Surabaya - Teguh Satrio; M. Robiul Fuadi (The Indonesian Journal of Occupational Safety and Health, 2020)
Introduction: Laboratory is a place for the analysis of a material that aims for research, education, quality testing and diagnose diseases. Working in the laboratory will always be faced with a variety of risk and sources of danger that can cause workplace accidents. The purpose of this study was to determine the hazards, hazard identification, risk identification, risk assessments, risk control, and residual risk in working at the clinical pathology laboratory. Method: Data collection method used was observational and descriptive research. When viewed from the time of the study, this study was cross sectional. The data used were primary and secondary data, in which the primary data were obtained by direct observation on site, while secondary data were obtained from SOPs available in the laboratory. Results: The results of the study can identify as many as 9 hazards. In the assessment of risk, it obtained the highest level of danger which was high risk. The level of risk was as high as 3 hazards including needling, splattered patient samples, and reagents or hazardous substances. Conclusion: The conclusion from the study is that this laboratory is classified as dangerous because it finds some of the highest risk levels, which is high risk. The existing risk control in this laboratory is quite complete and good, but it needs to be an improvement in terms of compliance in wearing Personal Protective Equipment (PPE) to minimize the risk.Keywords: clinical pathology laboratory, hazard identification, risk assessment